Respuesta :

I believe that the general form would be 2x +4y+ 2 = 3y + 5 
                                                                2x + 4y + 2 - 3y - 5 = 0
                                                                 2x + y - 3 = 0 

Answer:  The required general form of the given equation is

[tex]2x+y=3.[/tex]

Step-by-step explanation:  We are given to rewrite the following equation in general form :

[tex]2x+4y+2=3y+5~~~~~~~~~~~~~~~~~~~~~~~~~(i)[/tex]

We know that

the general form of a linear equation in two variables x and y is written as :

[tex]ax+by=c,~~\textup{[where a and b cannot be zero at the same time]}[/tex]

So, from equation (i0, we have

[tex]2x+4y+2=3y+5\\\\\Rightarrow 2x+4y-3y=5-2\\\\\Rightarrow 2x+y=3.[/tex]

Thus, the required general form of the given equation is

[tex]2x+y=3.[/tex]